Representation of Feminism Issues in Barbie the Movie: A Sociological Analysis - Aulia Tiara Rahmadanty (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze how feminist issues are portrayed in Barbie the Movie (2023) using a sociological approach, particularly gender theory, patriarchy, as well as liberal and radical feminist perspectives. The film is considered an important turning point in the representation of women in popular culture because it attempts to transform the long-standing image of the Barbie doll, which for years has been criticized for promoting unrealistic beauty standards. This research employs a qualitative descriptive method by analyzing the narrative and visual elements of key scenes in the film. The findings indicate that the film explicitly criticizes the patriarchal system, illustrates womens struggles within social structures, and offers a new depiction of womens existence. The study also reveals that Barbie the Movie is a product of popular culture that reflects contemporary social dynamics while providing broader insights into power relations between genders.